Results of testing of athletes in martial arts using the star excursion balance test method (on the example of women`s boxing, Kyokushinkai Karate, Fencing and WKF Karate) - Kindzer, B.; Nikitenko, S.; Vyshnevetskyi, S.; Kukurudziak, I.; Ilnytskyi, I.; Busol, V.; Bohdan, I.; Semeryak, Z.; Cynarski, W. J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Background. In the world scientific literature there is a lack of information regarding the Star Excursion Balance Test (SEBT) studies in combat sports. In our opinion, this technique can be successfully used not only for medical and rehabilitation purposes, but also for pedagogical and sports purposes.